Political Struggle as a Struggle for Leadership and Power - A. A. Zaikin (Управленческое консультирование, 2019)
Political struggle is rarely the subject of political research. It is so closely intertwined with the phenomenon of politics that it does not attract attention as an independent subject of research. The phenomenon of political struggle is always talked about, but what it is, its essence and content — goes by the wayside. The purpose of this article is to study the political struggle as a struggle for leadership and power. Political struggle in modern conditions is a complex sociopolitical phenomenon aimed at the transition of power to a certain political group (the conquest of power by a certain political class) in order to achieve certain political, economic, military and other interests. In his work, he highlights such forms of political struggle as parliamentary activity, revolutionary struggle, guerrilla movement. The concept of political struggle in the light of its analysis is broader in relation to the concept of conflict, as well as to the forms of its manifestation. Political struggle is a process that is not limited to the conflict, but includes the phases of formation of goals through propaganda and their implementation through the power status.